Intergeneration Transmission of Violence in Forensic Patients With a Diagnosis of Schizophrenia and Psychosis: Was Parental Alcoholic Abuse a Significant Factor? - Petrovic, Milena; Injac Stevovic, Lidija (Frontiers in Psychiatry, 2021)
Background: Child abuse during childhood and the presence of parental alcohol abuse increase the risk of developing mental illness in children, as well as the risk of violent behavior in adulthood. The association of these factors has not been sufficiently investigated when it comes to forensic mental patients. In this study, we examined the impact of traumatic events in childhood and the presence of mental illness and alcohol abuse of parents in subjects with psychosis and schizophrenia who committed serious crimes Methods: 143 respondents were included in the current study. Information on childhood abuse was collected by Childhood Trauma Questionnaire (CTQ). The sample included participants diagnosed with psychotic disorders and schizophrenia with a history of violent behavior (PSCH-V, n = 20), patients diagnosed with psychotic disorders and schizophrenia without a history of violent behavior (Non-V-PSCH, n = 51), and healthy control patients (HC, n = 72). Differences between groups in terms of traumatic events in childhood as well as parental alcohol abuse are presented and analyzed. Results: Statistically significant differences were obtained for total scores (χ2 = 28.522, p < .001) as well as for: major upheaval between the parents (χ2 = 20.739, p < .001), being victim of violence - other than sexual (χ2 = 12.701, p < .01), and other major upheaval that may have shaped life or personality significantly (χ2 = 30.920, p < .001). PSCH-V, compared to HC, had greater exposure to all of the three domains of childhood trauma (U = 396.500, U = 436.500, and U = 376.000, respectively; p < .001). Similar results were obtained when Non V-PSCH were compared with HC (U = 1223.000, U = 1535.000, and U = 999.000, respectively; p < .001). The presence of parental alcohol abuse was predominantly present in the PSCH-V group (60%) while a significantly lower presence was found in the Non-V PSCH group (35%) and HC (5.5%). Conclusion: Both PSCH-V and Non-V-PSCH groups had a high degree of exposure to traumatic events in childhood compared to the HC. In PSCH-V, the presence of parental alcohol abuse compared to Non-V-PSCH was dominant.